Genotyping of Rhodopirellula baltica organisms using multispacer sequence typing. (18th April 2013) - Cayrou, Caroline; Terra, Anthony; Drancourt, Michel
Abstract Rhodopirellula baltica is a ubiquitous Planctomycetes organism isolated from marine environments worldwide. Multilocus sequence analysis (MLSA) has been the only method used to assess the diversity of R. baltica organisms. Here, we developed multispacer sequence typing (MST) genotyping and applied it to four R. baltica isolates from the French Mediterranean Sea and R. baltica DSM10527T type strain. While MLSA yielded interpretable sequences for two of nine genes in three R. baltica isolates, MST based on sequencing two intergenic spacers yielded an unambiguous, strain‐specific profile for each one of the four R. baltica isolates under investigation. We propose that MST could be used as an alternative R. baltica genotyping method to assess the diversity of these Planctomycetes organisms.